Α-GLUCOSIDASE ENZYME INHIBITOR ACTIVITY OF ETLINGERA ELATIOR LEAF EXTRACT WITH SOLVENT VARIATION - Imrawati Imrawati; Yuri Pratiwi Utami; Yuniar Dwi Yanti; Tuti Handayani; Nurzadrina wahyuddin; Zahira Amody; Aulia Debby Pelu; Rahmah Mustarin; Indri Indri (JURNAL KATALISATOR, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin production or utilization. The increasing prevalence of diabetes, especially type 2, is a global concern due to the risk of complications it poses. One approach in treating type 2 diabetes is to inhibit the α-glucosidase enzyme to slow down glucose absorption. This research aims to identify the potential of patikala leaf extract as an α-glucosidase enzyme inhibitor. Using an experimental method with patikala leaf samples collected from Mariri Hamlet, Banyuurip Village, Bone-bone District, North Luwu Regency. Extraction was performed using the maceration method with variations in solvents: 70% ethanol, ethyl acetate, and n-hexane. The α-glucosidase enzyme inhibition activity was measured using a microplate reader and analyzed to determine the IC50 value. From the percentage inhibition data, the IC50 values obtained for 30% ethanol extract of patikala leaves were 351.95 µg/mL, for 70% ethanol extract of patikala leaves were 444.83 µg/mL, for 96% ethanol extract of patikala leaves were 362.27 µg/mL, for ethyl acetate extract of patikala leaves were 163.59 µg/mL, and for n-hexane extract of patikala leaves were 294.90 µg/mL, indicating that patikala leaf extracts with variations in solvent or extraction method exhibited very weak α-glucosidase enzyme inhibition activity. In conclusion, based on the research results obtained, the extract with variations in the solvent or extractant. Patikala leaf extract has an inhibitory activity against the α-glucosidase enzyme, which is categorized as very weak because it has an IC50 value > 100 µg/mL. In comparison, the control (acarbose) is in the weak category with an IC50 value of 50-100 µg/mL.